2011
DOI: 10.1111/j.1751-0813.2010.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential opportunistic infections in two German Shepherd dogs

Abstract: Two German Shepherd dogs with sequential opportunistic infections are described. The first was a 2-year-old male with cryptococcal rhinitis that spread to involve the optic nerves and brain. It was successfully treated with combination therapy utilising amphotericin B administered for 2 years, but the dog developed a disseminated Aspergillus deflectus infection 5 years later and was euthanased. The second case was a 4-year-old male that presented for a severe, deep-seated infection of the right antebrachium, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…This species is also common in indoor air (Houbraken et al 2007, Slack et al 2009) and is able to colonise water distribution systems (Hageskal et al 2011). Other species related to A. ustus can also cause human or animal infections; A. granulosus was found to cause disseminated infection in a cardiac transplant patient (Fakih et al 1995), while A. deflectus has been reported to cause disseminated mycosis in dogs (Jang et al 1986, Kahler et al 1990, Robinson et al 2000, Schultz et al 2008, Krockenberger et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…This species is also common in indoor air (Houbraken et al 2007, Slack et al 2009) and is able to colonise water distribution systems (Hageskal et al 2011). Other species related to A. ustus can also cause human or animal infections; A. granulosus was found to cause disseminated infection in a cardiac transplant patient (Fakih et al 1995), while A. deflectus has been reported to cause disseminated mycosis in dogs (Jang et al 1986, Kahler et al 1990, Robinson et al 2000, Schultz et al 2008, Krockenberger et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The third method, macrodilution (12,(19)(20)(21) or microdilution (7,8,22,23) in broth, utilizes the CLSI M38-A2 protocols (11) and inocula with final concentrations of 2 to 3 ϫ 10 3 zoospores/ml. Additionally, some studies have reported that P. insidiosum isolates were insensitive or resistant to all of the antimicrobials evaluated (24)(25)(26)(27) or described the MICs obtained by in vitro susceptibility tests (3,4,28) without describing how the inocula were prepared or how the susceptibility test was performed. This diversity in susceptibility testing techniques likely correlates with the diversity of MICs observed for P. insidiosum (see Table S2 in the supplemental material).…”
mentioning
confidence: 99%
“…The exact mechanism of their susceptibility to fungal infections is unclear; however, defects in mucosal immunity through IgA dysregulation (Day and Penhale ) and depressed local cellular responses (Pérez and others ) are possible. As a result of this susceptibility, recurrent and sequential fungal infections are reported in German shepherd dogs (Krockenberger and others ).…”
Section: Discussionmentioning
confidence: 97%